Teaching sport entrepreneurship in Malaysia: An educational design-based research / Payam Ansari - Payam , Ansari (2017)
An ‗entrepreneurial revolution‘ is taking over the world. Entrepreneurship is an important avenue for economic growth, job creation and social development. In agreeing with the controversial statement that ―Entrepreneurship can be taught‖, universities have dipped their toes into the lake of entrepreneurship, trying to shape their students as entrepreneurs. Although many scholars assert entrepreneurship education (EE) increases entrepreneurial intentions (EIs), statistics show that universities are not successful in this mission. Among academic disciplines, sport is one of those areas that despite enormous opportunities in the industry has produced fewer entrepreneurs than it intended. Numerous researchers have investigated the effects of EE on students‘ EI, but none have approached this issue from either the pedagogical perspective or the discipline of Sport. In fact, there is an evident gap in the studies that provide a systematic process of designing effective entrepreneurship courses. This study employed an educational design-based approach to develop a sport entrepreneurship course for sport students in Malaysia. The Ajzen‘s (1991) Theory of Planned Behaviour and Gagné‘s (1985) nine events of instructions were used as the theoretical foundation and teaching strategy guidelines of the course. The primary qualitative objective of this study was to determine the characteristics of an effective sport entrepreneurship course, and the main quantitative objective was to increase the students‘ EIs. The completed design was implemented through a pre-test/post-test quasi-experimental intervention with control group (that was not exposed to the course). A total of 52 students participated in this intervention. Chi-square and independent samples t-tests showed the experimental and control groups had no significant difference at the baseline. The statistical analysis results indicated that the students‘ EIs and Attitude toward Behaviour (ATB) increased significantly after the course. However, students‘ subjective norms and perceived behavioural control, despite showing a small improvement, did not change significantly after the course. Results showed that ATB was the strongest predictor of EIs. Furthermore, six months after the intervention, a follow-up enquiry was carried out. The findings identified that financial resources, lack of business knowledge and skills, and self-confidence were the most common setbacks toward self-employment, as perceived by study participants, who were fresh graduates when the follow-up enquiry was performed. This study was the first to take the instructional design aspect of an entrepreneurship course into account. Therefore, further studies, especially with experimental and action research approaches, are needed to investigate the influence of other pedagogical factors, such as various learning objectives, instructional designs, teaching methods, and etc.